Anaesthetic management for cardiac 3D electro‐anatomical mapping and radiofrequency catheter ablation in a horse with sustained atrial tachycardia. Issue 2 (28th February 2022) - Phillips, Victoria; Schauvliege, Stijn; Decloedt, Annelies; Van Steenkiste, Glenn; van Loon, Gunther
Abstract: Atrial arrhythmias in horses are common, and novel catheter‐based treatment techniques require the horse to be under general anaesthesia. A 3‐year‐old gelding, weighing 517 kg, presented for cardiac three‐dimensional electro‐anatomical mapping and radiofrequency ablation for treatment of sustained atrial tachycardia. The current case report describes a suitable anaesthetic protocol that included medetomidine and methadone as premedication, a combination of ketamine and diazepam for co‐induction of anaesthesia and maintenance with isoflurane vaporised in an oxygen/air mixture with constant‐rate infusions of medetomidine and lidocaine. Total anaesthesia time was 205 minutes. The current protocol did not negatively impact on the procedure performed, provided good haemodynamic stability for several hours and enabled a smooth, good‐quality recovery. The horse developed a triceps myopathy postoperatively, which was successfully treated and the horse was discharged 18 days following treatment.